2019
DOI: 10.3390/cancers11060747
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Impair Vasculogenic Mimicry from Glioblastoma Cells

Abstract: Glioblastoma (GBM), a high-grade glioma (WHO grade IV), is the most aggressive form of brain cancer. Available treatment options for GBM involve a combination of surgery, radiation and chemotherapy but result in a poor survival outcome. GBM is a high-vascularized tumor and antiangiogenic drugs are widely used in GBM therapy as adjuvants to control abnormal vasculature. Vasculogenic mimicry occurs in GBM as an alternative vascularization mechanism, providing a means whereby GBM can escape anti-angiogenic therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…85 A histone deacetylase inhibitor has also been identified as a promising candidate for VM inhibition in glioblastoma. 77,86 Finally, suppression of Axin1 87 and curA 88 have also been shown to affect VM.…”
Section: Cytokine Familymentioning
confidence: 98%
“…85 A histone deacetylase inhibitor has also been identified as a promising candidate for VM inhibition in glioblastoma. 77,86 Finally, suppression of Axin1 87 and curA 88 have also been shown to affect VM.…”
Section: Cytokine Familymentioning
confidence: 98%
“…There are limitations in the efficacy of single HDACis for GBM despite the tolerated toxicities that attribute to the poor pharmacokinetic properties and multiple misregulated growth and survival pathways in GBM. Thus it is rational to believe that the combinational treatment modality may represent an attractive approach to [151], I-BET151 [164], TSA [165], NaB [166], PB [167], FK228 [168], DATS [169], PXD-101 [170], NBM-HD-3 [171], Scriptaid [172], MS-275 [173] DR5, TNFα, p53, Bad, Bax, Bim, chop, Puma, m-calpian↑ proapoptotic genes SAHA [151], TSA [166], NaB [166], VPA [174], FK228 [152], DATS [169], PXD-101 [170], DWP0016 [175] vasculogenic mimicry, VEGF, EGFR↓ angiogenesis SAHA , MS-275, MC1568, TSA [176], NaB [177], DATS [169], LBH589 [178] Bcl2, Bcl-XL↓ antiapoptotic genes VPA [174], PB [167], FK228 [168], DATS [169] EZH2, MMP-2↓ invasion SAHA [179], VPA [174], FK228 [168], W2 [180] p-PTEN/p-AKT, pFAK/p-STAT3↓ pathways TSA [181], DATS [169], NBM-HD-3 [171], W2 [180] CDK2, CDK4, CDK6, cyclins D1, cyclins D2↓ progrowth genes SAHA [151], TSA [165] caspase 8, caspase 9, caspase 3 apoptotic cascade activation SAHA [182], DATS [169] HOTAIR↓ tumor pr...…”
Section: Hdacis-involved Combination Therapymentioning
confidence: 99%
“…In this study, we used CMap analysis to accurately identify compounds that have been shown to have specific effects on GBM or other tumor types by comparing the different expression genes of GMB samples from 3 clusters. These compounds include the DNA synthesis inhibitor anisomycin ( 73 ), glutamate receptor antagonist amantadine ( 74 ), norepinephrine inhibitor amitriptyline ( 75 , 76 ), solute carrier family member inhibitor bumetanide ( 77 ), PPAR receptor agonist clofibrate ( 78 ), and fenofibrate ( 79 ), selective serotonin reuptake inhibitor (SSRI) fluoxetine ( 75 , 80 ), ATPase inhibitor helveticoside ( 81 , 82 ), norepinephrine reuptake inhibitor imipramine ( 75 , 76 , 83 , 84 ), opioid receptor agonist loperamide ( 85 ), phosphodiesterase inhibitor papaverine ( 86 , 87 ) and rolipram ( 88 92 ), polar auxin transport inhibitor quercetin ( 93 , 94 ), cyclooxygenase inhibitor rofecoxib ( 95 , 96 ), calcineurin inhibitor tacrolimus ( 97 ), purinergic receptor antagonist ticlopidine ( 98 , 99 ), HDAC inhibitor vorinostat ( 100 ), Rho associated kinase inhibitor Y-27632 ( 101 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, it is still controversial whether some of the drugs identified by our study are effective against GBM. Such as vorinostat combined with bevacizumab significantly inhibited angiogenesis of GBM stem cells in vitro ( 100 ), but no significant benefit was observed in patients with GBM in clinical trials ( 113 ). However, our study provides evidence to explore the underlying mechanism of these drugs in the treatment of GBM, and it may be a new direction to investigate whether these drugs have the potential to treat GBM from a metabolic perspective.…”
Section: Discussionmentioning
confidence: 99%